Training the Pupilary Vision: Didactic Image, Slides, and Film in the Context of Media of the Late 19th Century - Česálková, Lucie (Teorie vědy / Theory of Science, 2011)
The study examines the modes of representation and communication of information through illustrative teaching aids in the 19th century. It focuses primarily on the didactic wall paintings and the tradition of lectures with slides and notes, how could the experience of these types of collectively observed images influence impressions and expectations of early film audiences. Didactic images are here analyzed primarily in terms of their compositional features (the arrangement of displayed objects within the frame), but in an effort to explain how processuality penetrated into the didactic image of the 19th century also with regard to the aspect of time. As a result, the study calls for a reassessment of the importance of the didactic wall painting in the formation of modern visuality and observational practices of the late 19th century.